Research on the construction of a service quality evaluation system for university student dormitories based on the Delphi method - Zhang, Caining; Zhao, Chunyu (Frontiers in Education, 2024)
Student dormitories play a pivotal role in the daily lives of university students in China, significantly influencing their academic, residential, and developmental experiences. However, there is a lack of a standardized framework to evaluate the service quality of these dormitories. This study aimed to develop a customized service quality evaluation index system specifically for Chinese university dormitories. The Delphi method and Analytic Hierarchy Process (AHP) were employed, involving 15 experts from Chinese universities. Two rounds of expert deliberation were conducted, starting with 28 initial indicators. The expert consultations resulted in the identification of six primary and 23 secondary indicators that form the service quality evaluation system. This framework is tailored to the specific needs of Chinese university dormitories and provides a solid technical foundation for future evaluations. It is expected to contribute to the improvement of dormitory management practices across China.